China's insolvency law and interregional cooperation comparative perspectives from China and the EU - Gong, Xinyi (The rule of law in China and comparative perspectives, 2018)
As a result of resumption of sovereignty over Hong Kong and Macao as well as the uncertain relationship between the Mainland and Taiwan, China has become a country composed of peculiar political compounds, resulting in four independent jurisdictions. This makes inter-regional legal cooperation a complicated yet compelling topic. The author discusses the advantages and disadvantages of the two systems and presents original recommendations for the way forward. The book will be a valuable resource for academics and policy makers in insolvency law, Asian law and comparative law.